Exploring the Feasibility of Implementing Flipped Classroom Concept in Engineering Education - Mohanta, Pulok Ranjan; Singh, Amit Kumar (Journal of Engineering Education Transformations, 2016)
With the rapidly changing global economy accompanied by faster up gradation of technology and frequent introduction of newer technologies into day to day life, it becomes necessary for almost everything to change in accordance to the present day scenario. This implies to the education field as well. And if we focus on professional course like engineering, the objectives of the courses can better be met by adapting to the present day scenario. In engineering education it becomes essential for the method of instruction to build the appropriate level of understanding of the concepts and phenomena that are taught during the lecture hour. To develop problem solving skill enough practice is also required. In earlier days the concept of teaching was like "sage on stage", wherein the lessons were delivered by teacher in the class room and students practice problems in their home. Though this method was the only option due to the unavailability of adequate technology, now new concept called Flipped Classroom is emerging which converts the classical concept of teaching to "guide by side". It tries to utilize the new common habit of the students to use technological devices worldwide. It can be observed that most of them spend much of their time accessing the internet for various purposes such as chatting on social media or accessing online materials (Fisher, 2009) Technology provides and shares the information instantaneously among the users, in college for example, the students and teacher can easily access the online contents of teaching and learning from their laptops, computers or Smartphone everywhere and anytime (Fu, 2013) This scenario gave an opportunity to emerge the concept of Flipped Classroom. This pedagogical method enables the better delivery of the lessons and helps the students develop better understanding of the concepts being taught. In this paper the author attempts to provide the concept and theory of implementing flipped learning approach for students and lecturers in engineering education.